Household's willingness to pay for heterogeneous attributes of drinking water quality and services improvement: an application of choice experiment - Dauda, Suleiman Alhaji; Yacob, Mohd Rusli; Radam, Alias (Faculty of Economics and Management, Universiti Putra Malaysia, 2012)
Drinking water of good quality and improved water related services have the efficacy to improve our living and health standard, large number of population especially in developing countries are lacking safe water for their daily sustenance, and the supply of such water from any source proves erratic. The objectives of this study are to assess the households’ demand preference of the heterogeneous water attributes in Damaturu, Yobe State, Nigeria and to estimate their marginal Willingness to pay, using Mixed Logit Model in comparison with Conditional Logit Model. Random sample of 300 households were surveyed, the result indicated that higher education influence greatly the households WTP decisions. The most significant variable in both the model is TWQ, which MRS from satisfactory to very good water quality in CLM is 219% in simple model and 126% for interaction model, MLM is 685% for simple model and 572% for interaction model. Estimate of MLM have more explanatory powers than CLM. Essentially, this finding can help the government in designing cost effective management and efficient tariff structure.